2007
DOI: 10.1111/j.1365-2435.2007.01272.x
|View full text |Cite
|
Sign up to set email alerts
|

Birthing asynchrony is not a consequence of asynchronous offspring development in a non‐avian vertebrate, the Australian skink Egernia whitii

Abstract: Summary 1.One of the major impediments to our understanding of avian hatching asynchrony is the difficulty in separating hypotheses that concentrate on the onset of incubation from those that explain hatching asynchrony adaptively. To address this, ideally we need a system(s) in which we can uncouple these two sets of hypotheses. Such a system exists in the skink genus Egernia . 2. We documented birthing asynchrony (analogous to hatching asynchrony) and the mechanisms underlying birthing asynchrony in the Whit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
56
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(56 citation statements)
references
References 43 publications
0
56
0
Order By: Relevance
“…In contrast, Stoleson & Beissinger () found no difference in survival of male and female parents raising synchronous or asynchronous broods. Asynchronous hatching and biparental care are not unique to birds, but also occur in some insects (Nalepa, ; Müller & Eggert, ) and reptiles (While, ). Thus, to improve our understanding of how asynchronous hatching contributes towards the resolution of sexual conflict over parental care, there is now a need to extend this work to nonavian systems.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Stoleson & Beissinger () found no difference in survival of male and female parents raising synchronous or asynchronous broods. Asynchronous hatching and biparental care are not unique to birds, but also occur in some insects (Nalepa, ; Müller & Eggert, ) and reptiles (While, ). Thus, to improve our understanding of how asynchronous hatching contributes towards the resolution of sexual conflict over parental care, there is now a need to extend this work to nonavian systems.…”
Section: Introductionmentioning
confidence: 99%
“…Asynchronous hatching is not restricted to altricial birds but is found in some insects where parents provide resources for their offspring, such as woodroach Cryptocercus punctulatus (Nalepa 1988) and burying beetle Nicrophorus vespilloides (Müller 1987, Müller and Eggert 1990, Smiseth et al 2006), and also in some social lizards, such as White's skink Egerina whitii (While et al 2007). Non‐avian species might provide valuable additional models to altricial birds for understanding the evolution of asynchronous hatching because hatching patterns are uncoupled from parental incubation (Smiseth et al 2006).…”
mentioning
confidence: 99%
“…Non‐avian species might provide valuable additional models to altricial birds for understanding the evolution of asynchronous hatching because hatching patterns are uncoupled from parental incubation (Smiseth et al 2006). Research on non‐avian species has so far focused on understanding the proximate mechanisms of hatching patterns (Smiseth et al 2006, While et al 2007). Recently, While and Wapstra (2008) found that, in White's skink, parents giving birth to asynchronous broods benefited from increased offspring growth but suffered from lower offspring survivorship compared to parents giving birth to synchronous broods.…”
mentioning
confidence: 99%
“…Although asynchronous hatching is reported from wide range of taxa, for example altricial birds (Magrath 1990;Stoleson and Beissinger 1995;Stenning 1996), amphibians (Ryan and Plague 2004), reptiles (While et al 2007), and insects (Nalepa 1988;Smiseth et al 2006;Takata et al 2013), previous studies have focused almost exclusively on avian species. In avian species, asynchronous hatching causes an age hierarchy in the offspring and usually results in establishment of competitive asymmetries within the brood.…”
Section: Introductionmentioning
confidence: 99%